PEMAKNAAN CERITA RAKYAT MELALUI KODE BAHASA ROLAND BARTHES - Insum Malawat (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Folklore is one of the nation’s cultural wealth to be preserved. Folklore tells about an incident in one place. Its function, in addition to the entertainment can also be used as paragon. This paper aims to reveal the meaning of cultural codes in the past who were in the three folklors who come from three regions: Legenda Danau Merah dan Danau Biru (Wamena), Pesan Terakhir Seorang Ibu (Maluku), dan Dewi Nawang Wulan (Jawa) as formal object. The third meaning of this folklore approach cultural code of Roland Barthes, the hermeneutic code, code semik, symbolic codes, code proretik, and cultural codes. Based on the results of the discussion is known that, in third folklore there are five language namely the code language of hermeneutics, semik code, symbolic codes, code proretik, and cultural codes. Third folklore has the same motive, namely breach of the message and mandate which its means a betrayal, infidelity, and disobediently. Consequently, betrayer must be punished.